A Comparative Study Of Surgical Outcome In Different Approaches For Hysterectomy - Tamrakar, Suman Raj (Journal of Nepalgunj Medical College, 2019)
Introduction: Globally, hysterectomy has been the commonest gynecologic surgery since a long time. One of the most remarkable innovations in surgery has been the changeover from laparotomy to laparoscopy. The first reported laparoscopic hysterectomy was in 1989 by Harry Reich, for endometriosis. As laparoscopic procedure has various important advantages over laparotomy, it has become a preferred surgical method. But open hysterectomy or laparoscopic hysterectomy has been chosen based on various factors and the surgeon’s experience and skill. Earlier hysterectomies were done in conventional way at Kathmandu University Hospital. But Laparoscopic assisted vaginal hysterectomy and total laparoscopic hysterectomy were started from 2011 and 2015 respectively. Method: This retrospective study was undertaken to compare the demographic parameters, operative particulars, postoperative outcomes including complications of different hysterectomy approaches done from 2011 to 2018 at Kathmandu University Hospital. Result: A total of 756 hysterectomy cases with 461 of open hysterectomy and 295 of laparoscopic hysterectomy were done in over 8 years. There was no significant difference in mean age of patients who underwent different types of hysterectomies (46.29±6.50 and 45.52±8.15 years, p=0.6829). There was significant increase in Brahmin/Chhetri caste seeking laparoscopic hysterectomy (p=0.0001) and significant decrease in other janajati caste undergoing laparoscopic hysterectomy (p=0.0004). The indications of different type of hysterectomy were almost comparable; with fibroids/adenomyosis (49.7%) followed by abnormal uterine bleeding (19.7%) were common indications. Laparoscopic hysterectomies have significantly increased since 2016. There were significant differences in operating time, blood loss and hospital stay between open and laparoscopic hysterectomy cases with 143.63±43.25 vs 67.56±25.75 minutes, 294.78±51.37 vs 470.24±102.99 ml and 2.61±0.66 vs 5.64±0.69 days respectively (all p<0.0001). There were 30 major complications in open and 10 in laparoscopic hysterectomy respectively with 9 minor complications in both. Eleven laparoscopy cases (3.7%) had to be converted to laparotomy. Conclusions: Laparoscopic hysterectomies are possible with equivalent advantages. A good laparoscopic experiences for surgeons and a careful selection of the cases are the obligatory prerequisites.